2003
DOI: 10.1002/int.10145
|View full text |Cite
|
Sign up to set email alerts
|

Incremental learning of collaborative classifier agents with new class acquisition: An incremental genetic algorithm approach

Abstract: A number of soft computing approaches such as neural networks, evolutionary algorithms, and fuzzy logic have been widely used for classifier agents to adaptively evolve solutions on classification problems. However, most work in the literature focuses on the learning ability of the individual classifier agent. This article explores incremental, collaborative learning in a multiagent environment. We use the genetic algorithm (GA) and incremental GA (IGA) as the main techniques to evolve the rule set for classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Incremental learning 12 is a popular technique that refers to learning controller behaviours by progressively increasing the complexity and/or scope of the learning task. It has been studied with several multi-agent domains [13][14][15][16] and has demonstrated successful results in comparison to direct evolution. Curriculum learning 17 is a relatively recent idea, which is an extension of incremental learning and is inspired by the curriculum and organisation of the education system which progressively introduces different concepts and examples.…”
Section: Abstraction Learning Architecturesmentioning
confidence: 99%
“…Incremental learning 12 is a popular technique that refers to learning controller behaviours by progressively increasing the complexity and/or scope of the learning task. It has been studied with several multi-agent domains [13][14][15][16] and has demonstrated successful results in comparison to direct evolution. Curriculum learning 17 is a relatively recent idea, which is an extension of incremental learning and is inspired by the curriculum and organisation of the education system which progressively introduces different concepts and examples.…”
Section: Abstraction Learning Architecturesmentioning
confidence: 99%
“…13,14 It is developed on the basis of a normal GA. Figure 1 illustrates the pseudocode of IGA. When a new attribute is ready to be integrated, an initial population is formed by integrating the old chromosomes (solutions) and new elements for the new attribute if available.…”
Section: Incremental Genetic Algorithm~iga!mentioning
confidence: 99%
“…This article uses the incremental genetic algorithm (IGA) as a basic evolutionary algorithm for incremental learning, 13,14 and proposes ordered incremental genetic algorithms (OIGAs) for the incremental training of input attributes for classifiers. Different from normal GAs, which learn input attributes in their full dimension, OIGAs learn the attributes one after another under a situation of continuous incremental learning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on machine learning datasets from UCI, Guan et al employed IAL to solve several classi¯cation and regression problems by neural networks and genetic algorithms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Almost all of their results using IAL were better than those derived from traditional methods. Speci¯cally, based on Incremental Learning in terms of Input Attributes (ILIA) 1 and ITID, two e®ective algorithms were developed on the basis of IAL, and as a result, classi¯cation errors obtained by incremental neural networks for input feature learning of Diabetes, Thyroid and Glass datasets reduced by 8.2%, 14.6% and 12.6% respectively.…”
Section: A Brief Introduction To Ialmentioning
confidence: 97%
“…This strategy makes the features with greater discrimination abilities be trained in an earlier step than others, and get rid of interference between features during classication. Previous studies showed that IAL can be independently employed and successfully applied based on many machine learning approaches, such as neural networks (NN), 1-8 genetic algorithms (GA), [9][10][11][12][13][14] decision trees (DT), 15 support vector machines (SVM), 16 and Bayesian classi¯er. 17 Apart from this,¯nal classi¯cation results produced by IAL also exhibit better performance than those derived by conventional one-batch training approaches.…”
Section: Introductionmentioning
confidence: 99%